2011
DOI: 10.5732/cjc.010.10402
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of unicentric mediastinal Castleman's disease

Abstract: Castleman's disease is a slowly progressive and rare lymphoproliferative disorder. Here, we report a 55-year-old woman with superior mediastinal Castleman's disease being misdiagnosed for a long term. We found a 4.3 cm mass localized in the superior mediastinum accompanied with severe clinical symptoms. The patient underwent an exploratory laparotomy, but the mass failed to be totally excised. Pathologic examination revealed a mediastinal mass of Castleman's disease. After radiotherapy of 30 Gy by 15 fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Chan et al 92 identified 17 cases of unresectable UCD in the literature treated with similar doses of radiotherapy. 53,85,87,88,90,91,[93][94][95][96][97][98] Thirteen achieved disease control, with 7 patients attaining a partial response and 6 a complete response. At a median follow-up of 20 months, only 1 had died as a result of progressive disease.…”
Section: Management Of Ucdmentioning
confidence: 99%
“…Chan et al 92 identified 17 cases of unresectable UCD in the literature treated with similar doses of radiotherapy. 53,85,87,88,90,91,[93][94][95][96][97][98] Thirteen achieved disease control, with 7 patients attaining a partial response and 6 a complete response. At a median follow-up of 20 months, only 1 had died as a result of progressive disease.…”
Section: Management Of Ucdmentioning
confidence: 99%
“…3,23 For disease that cannot be completely excised, radiation therapy is an option due to its high rates of objective response, including complete responses in nearly one-half of reported cases. [25][26][27][28][29][30][31] For select patients who are not candidates for surgical excision, but who are also not candidates for radiation therapy based on the location of the dis-ease, partial resection followed by clinical observation alone may result in lengthy remissions; however, such treatment warrants careful attention to local progression. Select patients who are asymptomatic with a low disease burden who cannot be treated with either surgery or radiation may be closely followed, given the often indolent nature of the disease.…”
Section: Managementmentioning
confidence: 99%
“…For patients with well-vascularized large tumors, preoperative angiography with selective embolization should be performed in order to reduce the bleeding risk. Radiotherapy is a viable alternative for the patients for whom the operative risks are too high or for whom a complete surgical excision is not possible, often this type of treatment providing good results [31][32][33][34][35][36][37]. Several studies have reported good results of neoadjuvant treatment in patients with large tumors -UCD, tumors that involved vessels like the vena cava, aorta, and iliac vessels.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Several studies have reported good results of neoadjuvant treatment in patients with large tumors -UCD, tumors that involved vessels like the vena cava, aorta, and iliac vessels. The neoadjuvant radiotherapy or rituximab has resulted in tumor downsizing, which further permitted surgical excision [34,38].…”
Section: Clinical Aspectsmentioning
confidence: 99%